If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/5x+1/3=10/15x+15
We move all terms to the left:
1/5x+1/3-(10/15x+15)=0
Domain of the equation: 5x!=0
x!=0/5
x!=0
x∈R
Domain of the equation: 15x+15)!=0We get rid of parentheses
x∈R
1/5x-10/15x-15+1/3=0
We calculate fractions
75x^2/675x^2+135x/675x^2+(-450x)/675x^2-15=0
We multiply all the terms by the denominator
75x^2+135x+(-450x)-15*675x^2=0
Wy multiply elements
75x^2-10125x^2+135x+(-450x)=0
We get rid of parentheses
75x^2-10125x^2+135x-450x=0
We add all the numbers together, and all the variables
-10050x^2-315x=0
a = -10050; b = -315; c = 0;
Δ = b2-4ac
Δ = -3152-4·(-10050)·0
Δ = 99225
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{99225}=315$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-315)-315}{2*-10050}=\frac{0}{-20100} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-315)+315}{2*-10050}=\frac{630}{-20100} =-21/670 $
| 7(x+7)-9=-2x+9(x+4) | | 6h-(9-3h)=6-3 | | 11x-9+3x+8=2x+9+12x-10 | | 6(8x-5)=354 | | 12(p-4)=(6p+10) | | 3(x+9)^=54 | | 8/x=24/15 | | 18x+63=4x+14 | | 5a/2=2a+5 | | 0.2-1/x^2=0 | | 3x²+4×−2=0 | | 3(2x+4)=9x+9-3x+3 | | 9+6x=8x-13 | | 7v/10+2=5v/6 | | (x-3)⋅(x+2)=2x-6 | | (y+3)(3y-6)=0 | | x^-2-72=0 | | 2c+8=|10c| | | (y=3)(3y-6)=0 | | (x-3)⋅(x+2)-(2x-6)=0 | | 8y+4=2y-2 | | x-4/12=3/2 | | 3+x√2=-√2 | | -4(b+8)=-1+3(-b-5) | | 2m^2-2m-1.5=0 | | 3(w-1)=w+1-2(-7w-6) | | 1/x^2=0.2 | | 4/5y=1/6 | | -8(4+9x)=7(-2-11x | | x+3=x*1.25 | | 3(9q-)=9q-27 | | 11/7x+49-2/x+7=5/7 |